Regulating Chlorophyll a to Control DBP Precursors in Water Supply Reservoirs. Issue 11 (1st November 2015) - Saunders, James F.; Hohner, Amanda K.; Summers, R. Scott; Rosario‐Ortiz, Fernando L.
Abstract : Colorado recently adopted a chlorophyll a standard of 5 μg/L as an option for additional protection of direct‐use water supply reservoirs. Setting a limit on algal abundance by regulating chlorophyll a in these reservoirs is a preventive measure aimed at controlling or reducing algal‐derived precursors of disinfection by‐products (DBPs). Development of the chlorophyll a standard was based on field studies of Colorado reservoirs and compliance data from the associated water treatment systems. Controlling algal abundance in these reservoirs can supplement conventional treatment or serve as an alternative to additional treatment in situations in which algae contribute significantly to the organic precursors that can form DBPs during treatment. The focus on algae is important because algal‐derived precursors are difficult to remove during conventional water treatment and because algal abundance can be controlled via the nutrient supply.